Lokale organisasjoner med en nasjonal overbygning. Brannkassene og Samtrygd 1914–1939 - Harald Espeli (Heimen)
Abstract From the 1890s to World War I, the fire insurance mutuals had insured larger values than their main competitor, the state-owned Norges Brannkasse, in the countryside. In 1922 twenty-three local fire insurance mutuals established a common reinsurance mutual, Samtrygd, which also functioned as an umbrella organisation for an increasing number of members. The main initiators behind Samtrygd were not the fire insurance mutuals, which were predominantly locally oriented, but the Farmer’s Union and a commercial bank, Bøndernes Bank, which guaranteed Samtrygd’s start-up costs. Samtrygd solved one of the structural weaknesses of the local fire insurance mutuals: lack of a cost-efficient reinsurance, which was necessary to insure ever more expensive buildings and chattel. From the late 1920s, more than half of local fire insurance mutuals were members of Samtrygd. Thus, with the assistance of Samtrygd the local fire insurance mutuals were able to consolidate their market position in countryside in the inter-war period despite the fact that fire insurance continued to be the only form of non-life insurance they could offer. Their core customers and members, the farmers, bought cars and lorries in significant numbers which demanded other forms of non-life insurance. Samtrygd’s initiators had planned that the fire insurance mutuals should expand into more densely populated areas and possibly the suburbs in the municipalities in the countryside. However, the fire insurance mutuals, governed by the local farmer elite, decided to stick to their last, and abstained from engaging in the growing markets in such areas.